EFFECTS OF MIGRANT REMITTANCES ON FARM HOUSEHOLD WELFARE IN NIGERIA - Egbe BASSEY ETOWA; Noble J. NWEZE; Chukwuemeka J. ARENE (Review of Agricultural and Applied Economics, 2015)
International remittances are now a mechanism in development financing and a welfare strategy. Growing trends of these money transfers by migrants to their families back home in developing nations have been proven by evidences in literature and many empirical findings. This research analysed the effects of migrant remittances on the welfare of farm households in Nigeria. Welfare was measurable in terms of the households’ real per capita consumption. Cross sectional data were pooled from two sources. The data sources were Nigerian General Household Survey conducted in 2010/2011 and the Nigerian Living Standard Survey carried out in 2003/2004. The analytical technique adopted was the poverty profile function within the framework of multiple regression analysis. Results showed that four exogenous variables, including household real per capita remittances were significant determinants of household real per capita consumption (welfare).